The Evolution of Mechanisms Driving the Stomatal Response to Vapor Pressure Deficit . Issue 3 (30th January 2015) - McAdam, Scott A.M.; Brodribb, Timothy J.
Abstract : The mechanism for a stomatal response to vapor pressure deficit evolved from a passive regulation in basal vascular plants to mediation by ABA in the earliest angiosperms. Abstract: Stomatal responses to vapor pressure deficit (VPD ) are a principal means by which vascular land plants regulate daytime transpiration. While much work has focused on characterizing and modeling this response, there remains no consensus as to the mechanism that drives it. Explanations range from passive regulation by leaf hydration to biochemical regulation by the phytohormone abscisic acid (ABA ). We monitored ABA levels, leaf gas exchange, and water status in a diversity of vascular land plants exposed to a symmetrical, mild transition in VPD . The stomata in basal lineages of vascular plants, including gymnosperms, appeared to respond passively to changes in leaf water status induced by VPD perturbation, with minimal changes in foliar ABA levels and no hysteresis in stomatal action. In contrast, foliar ABA appeared to drive the stomatal response to VPD in our angiosperm samples. Increased foliar ABA level at high VPD in angiosperm species resulted in hysteresis in the recovery of stomatal conductance; this was most pronounced in herbaceous species. Increased levels of ABA in the leaf epidermis were found to originate from sites of synthesis in other parts of the leaf rather than from the guard cells themselves. The transition from a passive regulation to ABA regulation of the stomatal response to VPD in the earliest angiosperms is likely to have had critical implications for the ecological success of this lineage.